Improved physicochemical stability and bioaccessibility of astaxanthin-loaded oil-in-water emulsions by a casein-caffeic acid–glucose ternary conjugate. (January 2023) - Cheng, Jingrong; Shen, Shuangwei; Yang, Huaigu; Tang, Daobang; Wang, Xuping; Lin, Yaosheng; Liu, Xueming
Graphical abstract: Highlights: Casein-caffeic acid–glucose conjugate (CSC) can stabilize the emulsion. The CSC-stabilized emulsion is more stable than sodium caseinate (CSN) emulsion. The CSC emulsion showed better astaxanthin protection than CSN emulsion. The bioaccessibility of astaxanthin in CSC-stabilized emulsion was higher than that in CSN. Abstract: In this study, the influence of casein-caffeic acid–glucose ternary conjugate (CSC) on the physicochemical properties and bioaccessibility of astaxanthin-loaded emulsion was investigated and compared with sodium caseinate (CSN), a synthetic emulsifier commonly used in the food industry. The CSC-stabilized emulsion exhibits droplet characteristics similar to CSN-stabilized emulsion, and can effectively resist the external forces that lead to the phase separation of the emulsion. Although phase separation also occurred at pH 4.0, CSC emulsion had a wider range of pH stability (pH 3.0, 5.0–8.0) and higher salt ion stability than CSN emulsion. Furthermore, CSC-stabilized astaxanthin emulsions showed better astaxanthin protection under different heat treatment conditions and storage temperatures compared with CSN. After 28 days of storage at 4 °C, astaxanthin residues in the CSC-stabilized emulsion reached 92.37 %. The bioaccessibility of astaxanthin in CSC-stabilized emulsion was 26.21 %, much higher than that in CSN (6.47 %). This research study provides a platform for designing astaxanthin-fortified food or beverage systems to achieve better stability and delivery to target sites.